2020
DOI: 10.4103/aer.aer_9_20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative dexmedetomidine on postoperative pain and pulmonary function following video-assisted thoracoscopic surgery

Abstract: Context: Acute postoperative pain following video-assisted thoracoscopic surgery (VATS) needs considerable attention, if untreated leads to chronic pain and postoperative lung dysfunction. Dexmedetomidine, α 2 adrenoceptor agonist has shown promising results of opioid-sparing effects. Aims: The objectives of this study are to investigate the effect of dexmedetomidine on postoperative analgesia and pulmonary mechanics in patients undergoing VAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Jannu et al. [ 13 ] also compared two groups of patients receiving either i.v. dexmedetomidine or saline.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Jannu et al. [ 13 ] also compared two groups of patients receiving either i.v. dexmedetomidine or saline.…”
Section: Resultsmentioning
confidence: 99%
“…We recommend intra‐operative use of i.v. dexmedetomidine because two studies documented that it reduces pain scores and opioid demand [ 12 , 13 ]. Dexmedetomidine also decreased the incidence of postoperative agitation and cognitive dysfunction, and postoperative nausea and vomiting [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…106 In patients undergoing VATS, evidence has shown that intraoperative dexmedetomidine can reduce postoperative pain, patient satisfaction, and improve pulmonary mechanics. 107,108 Data regarding the benefit of postoperative administration are unclear because of mixed results and heterogenous administration regimens between studies. 109,110 In open cardiac surgery, studies using dexmedetomidine have demonstrated less postoperative delirium, 111 kidney injury, 112 and death.…”
Section: Systemic Therapiesmentioning
confidence: 99%